Who Is The Target Market Of Digital Tourism 4.0? - Felix Goenadhi; Dedi Rianto Rahadi (President University, 2020)
This study is to investigate the willingness or intention of millennials and Gen Z era because nowadays, they are the new target market and their tourism destination image to visit several places in Indonesia based YouTube account